Marium's Birthday (big book) - Nooren, Farah (Notre Dame Karachi, 1998)
"Marium's Birthday" follows a young girl named Marium as she gets ready for her birthday celebration. Excitement builds as she plans her party, invites her friends, and prepares delicious treats. Along the way, she learns about the importance of friendship, sharing, and making special memories. The story highlights the joy of celebrating with loved ones and the fun of a birthday party.